Smoking and life-course events among youths living in Area C of the occupied Palestinian territory: an analysis of data from the Palestinian Family Health Survey. (August 2017) - Abu-Nabaa, Hendia A; Abu-Rmeileh, Niveen
Abstract: Background: Individuals' maturity, independence, and freedom of choice involve five risky behaviours; smoking is the one that most seriously affects individual and public health. Since OSLO accord in 1993, 60% of the West Bank has been under Israeli military control (known as Area C) and is home to about 300 000 Palestinians and a settler population of at least 325 500 people. Israel retains the area to serve military training, economic interests, and settlement development, potentially affecting Palestinian people's life course. We aimed to compare smoking and life-course events among youths aged 14–29 years in 2010 living in Palestinian areas under Palestinian control (PA) of the West Bank and Gaza Strip (population 837 099 youths) with those residing in Area C (population 90 000 youths) in the West Bank. Methods: We used data from the Palestinian Family Health Survey (which was done by the Palestinian Centre Bureau of Statistics in 2010), in which smoking was the dependent variable. A youth's life-course events, including school enrolment, employment status, marital status, combined with employment (ie, married and employed), and waiting (ie, not married, employed, or studying), were regarded as independent variables in addition to other important factors using SPSS software (version 17). Findings: 25 484 youths were included in the analyses (1714 [7%] living in Area C and 24 132 [93%] living in PA). 255 (15%) youths in Area C were smokers compared with 3163 (13%) in PA. Bivariate analyses showed a significant association between smoking statuses and sex (p≤0·05), age (p≤0·05), life course (p≤0·05), region of residency (p≤0·05), wealth-index quintiles (p≤0·05), and area (p≤0·05). Logistic regression showed that youths living in Area C were more likely to smoke than those living in PA (odds ratio [OR] 1·55, 95% CI 1·29–1·86). Moreover, more youths reported to be smokers who were employed and married (41·6%) than workers not married (38·9%) and waiting (19·1%). Youths older than 17 years were more likely to smoke (aged 18–25 years: OR 4·19, 95% CI 3·63–4·85; aged 26–29 years: OR 5·45, 4·55–6·53) than were those aged younger than 17 years. Those living in the West Bank were more likely to smoke than those living in Gaza (4·70, 4·19–5·27). Living in rural refugee camps doubled the probability of being smokers than living in urban camps (1·48 1·27–1·72). Finally, men had an increased probability to be smokers compared with women (74·02, 57·70–94·98). Of youths living in Area C, only students were most likely to smokers. In PA, unemployed youths and students were both most likely to be smokers. Interpretation: Additional in-depth research is needed to understand the coping mechanisms used by youths to reach adulthood under stressful situations. A limitation of our study was that socioeconomic status was not included in the statistical model. Funding: None.